2011
DOI: 10.3109/1061186x.2011.589435
|View full text |Cite
|
Sign up to set email alerts
|

Brain-targeted delivery of paclitaxel using glutathione-coated nanoparticles for brain cancers

Abstract: Paclitaxel is not effective for treatment of brain cancers because it cannot cross the blood-brain barrier (BBB) due to efflux by P-glycoprotein (P-gp). In this work, glutathione-coated poly-(lactide-co-glycolide) (PLGA) nanoparticles (NPs) of paclitaxel were developed for brain targeting for treatment of brain cancers. P-gp ATPase assay was used to evaluate the NP as potential substrates. The NP showed a particle size suitable for BBB permeation (particle size around 200 nm) and higher cellular uptake of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 28 publications
8
84
0
Order By: Relevance
“…Glutathione-coated PEG-PLGA NPs (237 nm) with entrapped paclitaxel showed significantly higher therapeutic efficiency than uncoated NPs and paclitaxel solution. Tubulin immunofluorescent and Western blotting studies also confirmed the enhanced therapeutic efficacy of paclitaxel entrapped in glutathione-coated NPs [32] .…”
Section: Therapeutic Efficacymentioning
confidence: 65%
See 3 more Smart Citations
“…Glutathione-coated PEG-PLGA NPs (237 nm) with entrapped paclitaxel showed significantly higher therapeutic efficiency than uncoated NPs and paclitaxel solution. Tubulin immunofluorescent and Western blotting studies also confirmed the enhanced therapeutic efficacy of paclitaxel entrapped in glutathione-coated NPs [32] .…”
Section: Therapeutic Efficacymentioning
confidence: 65%
“…A number of in vitro experiments have demonstrated that surface functionalized NPs enhanced the therapeutic efficacy of antitumor drugs against the glioma cells such as RG2 and C6 glioma cells when compared with that of free drugs in solution and unmodified NPs with entrapped drugs [17,20,28,32,37,41] . Besides cell viability, IC 50 , the concentration of the drug required to kill 50 % of the incubated cells over a fixed time period, was employed to quantify and evaluate the cytotoxicity of NPs loaded with chemotherapeutic drugs, and their therapeutic efficiency.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Systemically-administered poly(lactic acid) (PLA) NPs, loaded with breviscapine (a flavonoid), have been shown to penetrate the BBB (Liu et al 2008). Geldenhuys et al (2011) have demonstrated that surface modification of paclitaxel-loaded PLGA NPs with glutathione may also improve BBB bypass. Surface functionalization with PEG-PLA NPs with lectins like wheat gram protein, which specifically bind to the sialic acid present in large amounts in nasal cavities, have shown to increase brain uptake enormously (Gao et al 2006).…”
Section: Nanomaterials In Drug Deliverymentioning
confidence: 99%